2021
DOI: 10.5194/acp-21-12867-2021
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Evaluation of profile retrievals of aerosols and trace gases for MAX-DOAS measurements under different aerosol scenarios based on radiative transfer simulations

Abstract: Abstract. Ground-based Multi-AXis Differential Optical Absorption Spectroscopy (MAX-DOAS) is a state-of-the-art remote sensing technique for deriving vertical profiles of trace gases and aerosols. However, MAX-DOAS profile inversions under aerosol pollution scenarios are challenging because of the complex radiative transfer and limited information content of the measurements. In this study, the performances of two inversion algorithms were evaluated for various aerosol pollution scenarios based on synthetic sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The results indicated that the effect of vertical resolutions for the Lidar profiles as aerosol information on NO 2 profile retrieval was insignificant. This finding aligns with previous reports [22], confirming that the retrieved NO 2 profiles were consistent based on the input aerosol profile and the retrieved aerosol profile.…”
Section: Lidar Profiles As Aerosol Profiles In No 2 Profile Retrievalssupporting
confidence: 92%
See 3 more Smart Citations
“…The results indicated that the effect of vertical resolutions for the Lidar profiles as aerosol information on NO 2 profile retrieval was insignificant. This finding aligns with previous reports [22], confirming that the retrieved NO 2 profiles were consistent based on the input aerosol profile and the retrieved aerosol profile.…”
Section: Lidar Profiles As Aerosol Profiles In No 2 Profile Retrievalssupporting
confidence: 92%
“…In this study, the PriAM algorithm, based on the SCIAMACHY radiative transfer model (SCIATRAN), which was used to retrieve trace gas VCDs and profiles, was developed by the Anhui Institute of Optics and Fine Mechanics, Chinese Academy of Sciences (AIOFM, CAS), in cooperation with the Max Planck Institute for Chemistry (MPIC) [24,37,38]. PriAM also consists of a two-step inversion procedure based on the optimal estimation method (OEM) [8,18,22,27,39]. PriAM can retrieve trace gas and aerosol profiles for any arbitrary vertical grid.…”
Section: Profile Retrievalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then the O 4 DAMF α and the look-up table method are applied to retrieve the aerosol profile information. [12,13] Finally the trace gas profile information is retrieved by the trace gas DSCD α and look-up table method. The look-up table method [5,6] employs finite parameters to represent the aerosol extinction profile and trace gas vertical profile, which include aerosol optical depth (trace gas is VCDs), the boundary layer height, the weight factor of NO 2 in the boundary layer, etc.…”
Section: Retrieval Principle Of No 2 Profilementioning
confidence: 99%